Research and Development of the Pupil Identification and Warning System using AI-IoT - Trinh Luong Mien; Vo Van An; Thi Thu Huong (Journal of Robotics and Control (JRC), 2022)
Currently, pupils being left in the classroom, in the house or in the car is happening a lot, causing unintended incidents. The reason is that parents or caregivers of pupils go through busy and tiring working hours, so they accidentally leave pupils in the car, indoors, or forget to pick up students at school. In this paper, we developed an algorithm to recognize students who use neural networks and warn managers, testing on a model integrated Raspberry Pi 4 kit programmed on Python in combination with cameras, sim modules, and actuators to detect and alert abandoned pupils to the manager to take timely remedial measures and avoid unfortunate circumstances. With the ability to manage students, the system collects and processes images and data on student information for artificial intelligence (AI) systems to recognize when operating. The system of executive structures serves to warn when students are left in the car, in the classroom, or in the house to avoid unintended incidents or safety risks.